2016
DOI: 10.1093/dnares/dsw051
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing in tomato pollen in response to heat stress

Abstract: Alternative splicing (AS) is a key control mechanism influencing signal response cascades in different developmental stages and under stress conditions. In this study, we examined heat stress (HS)-induced AS in the heat sensitive pollen tissue of two tomato cultivars. To obtain the entire spectrum of HS-related AS, samples taken directly after HS and after recovery were combined and analysed by RNA-seq. For nearly 9,200 genes per cultivar, we observed at least one AS event under HS. In comparison to control, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 80 publications
4
69
0
Order By: Relevance
“…More than 42% of Arabidopsis intron containing gene produces more than one transcript (Filichkin et al, ). Stress‐responsive changes in alternative splicing pattern has been demonstrated in several plant species caused by heat, cold, and salt stress (Bournay, Hedley, Maddison, Waugh, & Machray, ; Egawa et al, ; Keller et al, ; Matsukura et al, ; Marquez, Brown, Simpson, Barta, & Kalyna, ; Shang, Cao, & Ma, ). The previous studies, involving RNA‐seq based alternative splicing or protein family and isoform analysis, demonstrated repeated occurrence of stress‐responsive alternative splicing and generation of splice variants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 42% of Arabidopsis intron containing gene produces more than one transcript (Filichkin et al, ). Stress‐responsive changes in alternative splicing pattern has been demonstrated in several plant species caused by heat, cold, and salt stress (Bournay, Hedley, Maddison, Waugh, & Machray, ; Egawa et al, ; Keller et al, ; Matsukura et al, ; Marquez, Brown, Simpson, Barta, & Kalyna, ; Shang, Cao, & Ma, ). The previous studies, involving RNA‐seq based alternative splicing or protein family and isoform analysis, demonstrated repeated occurrence of stress‐responsive alternative splicing and generation of splice variants.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins are shown to interact and regulate important cellular pathways including ubiquitin-mediated degradation (blue), miRNA biogenesis and degradation (green), and flowering and circadian clock maintenance related proteins (pink). Besides these major pathways, several other known and uncharacterized proteins were found to show strong interaction with the core splicing-related protein complex Egawa et al, 2006;Keller et al, 2016;Matsukura et al, 2010;Marquez, Brown, Simpson, Barta, & Kalyna, 2012;Shang, Cao, & Ma, 2017 Our future efforts would focus on functional annotation of the novel candidates and clarify their role in stress tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have investigated the AS responses under heat and drought stress in different plant species; however, a parallel comparison of AS responses induced by these two conditions has not yet been reported (Chang et al, 2014;Jiang et al, 2017;Keller et al, 2016;Thatcher et al, 2016). Our results indicated that much stronger AS responses were induced by HS and HD than by DS, while the transcriptional responses were found comparable under these three conditions, suggesting that DS response was mainly due to transcriptional modulation, whereas HS and HD responses could be attributed to both AS (DSGs) and transcriptional regulation (DEGs) in wheat seedling leaves (Figures 2a, 4a and S6).…”
Section: As and Transcriptional Modulations Cooperate To Finetune Hs mentioning
confidence: 99%
“…Genome-wide investigation of AS in moss (Physcomitrella patens) has identified 1779 AS events significantly responsive to elevated temperature, accounting for nearly half of expressed genes (Chang et al, 2014). Furthermore, approximately 7500 genes with HS-dependent accumulation of IR and ES were detected in tomato (Solanum lycopersicum) pollen, including six HSFs and 29 HSPs, which play key roles in plant heat shock response (Keller et al, 2016). However, comprehensive comparison of AS responsive to heat, drought and their combination is still not available in plant.…”
Section: Introductionmentioning
confidence: 99%
“…Several traits have been implicated in heat stress tolerance in tomato including membrane thermo stability (MTS), floral characteristics, cone splitting, pollen viability, fruit set and fruit yield [8]- [13]. High temperature at the reproductive stage of development causes significant flower drop [14] resulting in decreased fruit set and yield [15].…”
Section: Introductionmentioning
confidence: 99%